Analysis of the nutritional status and needs of 11-year-old primary school students - Kadek Ratna; Hendra Mashuri; I Ketut Semarayasa (Universitas Sriwijaya, 2025)
Research Problems: Optimal nutritional status is crucial for the physical and cognitive development of elementary school students aged 11 years. However, there are still gaps in meeting their nutritional needs, which may affect their health and academic performance. Research Objectives: This study aims to analyze the nutritional status and needs of fifth-grade students at SD N 3 Tamblang. Methods: This research is a descriptive quantitative study using a survey method. Results: The findings indicate that among the 31 students examined, 2 students (7%) were classified as severely obese, 13 students (42%) had a normal/ideal nutritional status, 6 students (19%) were mildly underweight, and 10 students (32%) were severely underweight. No students were categorized as mildly obese (0%). The analysis of macronutrient needs showed an average carbohydrate requirement of 367.29 grams (range: 311–462 grams), an average protein requirement of 91.82 grams (range: 78–115 grams), and an average fat requirement of 68.02 grams (range: 58–86 grams). Conclusion: The nutritional status of fifth-grade students at SD N 3 Tamblang indicates that some students have not yet achieved optimal nutritional status. Therefore, intervention from Physical Education teachers and parents is needed to improve children's nutritional quality.